Parceria p??blico privada e a gest??o de parques urbanos no municipio de S??o Paulo: percep????o de especialistas - Viana, Neiva Menezes (2019)
The use of the Public-Private Partnerships model is growing in Brazil, highlighting innumerable projects in the country in the planning stages, in execution and already finalized. According to the literature, the partnerships seek to achieve efficiency in management resulting in savings for public coffers and improvement of Public Administration. Green spaces, such as public parks, bring many contributions to the population, one of the most important being the improvement of the quality of life, contemplating social and psychological aspects. Among the environmental problems caused by human activities is the reduction of green areas, indicating that the greater the urbanization the greater the reduction of these spaces. In this context, the city of S??o Paulo reached its goal of reaching the number of 100 municipal parks by the year 2012. However, the management and maintenance of these spaces has become a challenge for public administration, where the solution is geared towards a public and private partnership. In this sense, the present study analyzed the perception of specialists for the current scenario of a Public Private Partnership, as well as evaluated the perception of these experts for the contributions of PPP???s to the management of Urban Parks. One of the research techniques used for data collection was a structured interview with specialists using the snowball method. All the interviews were recorded and transcribed by the author and later analyzed in the ATLAS T.I Software. The content analysis consisted of a pre-analysis of the expert's speeches, and in a second moment, the excerpts of the speech were categorized. Among the main results, it is worth noting that in the experts' perception the benefits of PPP???s are related to an improvement in the quality of the services provided and reduction of public costs, once the risks are shared. According to the experts' perception, the present study points out those PPP???s have numerous benefits in Brazil and also for the park management in S??o Paulo in the common concession model. The research can help the government to have a better dialogue and transparency with the population, as well as better the quality of services provided.